2019
DOI: 10.14814/phy2.13984
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebral autoregulation is attenuated in young fit women

Abstract: Young women exhibit higher prevalence of orthostatic hypotension with presyncopal symptoms compared to men. These symptoms could be influenced by an attenuated ability of the cerebrovasculature to respond to rapid blood pressure (BP) changes [dynamic cerebral autoregulation (dCA)]. The influence of sex on dCA remains unclear. dCA in 11 fit women (25 ± 2 years) and 11 age‐matched men (24 ± 1 years) was compared using a multimodal approach including a sit‐to‐stand (STS) and forced BP oscillations (repeated squat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 45 publications
3
90
4
Order By: Relevance
“…To evaluate the change in P ETCO 2 for each squatting frequency, the first and last five breaths were averaged. The difference between these two values represents the change in P ETCO 2 across that frequency as previously reported (Labrecque et al, 2019).…”
Section: Data Analysis 261 Baseline and P Etco 2 Datamentioning
confidence: 59%
See 2 more Smart Citations
“…To evaluate the change in P ETCO 2 for each squatting frequency, the first and last five breaths were averaged. The difference between these two values represents the change in P ETCO 2 across that frequency as previously reported (Labrecque et al, 2019).…”
Section: Data Analysis 261 Baseline and P Etco 2 Datamentioning
confidence: 59%
“…The female cohort was also limited to three individuals in the sedentary group. Some authors report improved dCA in women compared to males (Favre & Serrador, ), whilst others report a reduction in dCA capacity in endurance‐trained females compared to age‐matched, endurance‐trained males (Labrecque et al., ). Abidi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the modality of exercise performed by individuals has appreciable effects on the cerebral pressure‐flow response. As such, future investigations will need to also consider the modality of exercise performed and potentially the sporting background (Perry et al, ) of subjects as the potential long‐term exposure to MICT and/or HIIT patterns may differentially alter cerebral autoregulatory capacity (Drapeau et al, ; Labrecque et al, ; Lind‐Holst et al, ). Taken together, the results from this investigation demonstrate that refraining from exercise for 12–24 hr prior to dynamic CA data collection is excessively conservative.…”
Section: Discussionmentioning
confidence: 99%
“…An attenuated dynamic cerebral autoregulation (dCA), which describes the ability of the cerebrovasculature to respond to rapid changes in mean arterial pressure (MAP), in the posterior cerebral circulation could accentuate the reduction in blood supply to posterior regions of the brain following acute MAP reduction, which in turn could explain the appearance of symptoms in women during orthostatic stress. However, although we previously reported that healthy young fit women display diminished dCA in the MCA compared to men (Labrecque et al, 2019a), whether a differential dCA response between MCA and PCA in these young fit women remains to be clearly determined.…”
Section: Introductionmentioning
confidence: 79%